2015
DOI: 10.1093/nar/gku1377
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide features of neuroendocrine regulation in Drosophila by the basic helix-loop-helix transcription factor DIMMED

Abstract: Neuroendocrine (NE) cells use large dense core vesicles (LDCVs) to traffic, process, store and secrete neuropeptide hormones through the regulated secretory pathway. The dimmed (DIMM) basic helix-loop-helix transcription factor of Drosophila controls the level of regulated secretory activity in NE cells. To pursue its mechanisms, we have performed two independent genome-wide analyses of DIMM's activities: (i) in vivo chromatin immunoprecipitation (ChIP) to define genomic sites of DIMM occupancy and (ii) deep s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 94 publications
(158 reference statements)
2
27
0
Order By: Relevance
“…Next we sought a link between Dimm and wingless signaling and noted that some direct targets of Dimm may be involved in exosome release (see Hadzic et al, 2015 ). The exosome-dependent release of Wg requires the transmembrane protein Evenness Interrupted (Evi) ( Koles et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next we sought a link between Dimm and wingless signaling and noted that some direct targets of Dimm may be involved in exosome release (see Hadzic et al, 2015 ). The exosome-dependent release of Wg requires the transmembrane protein Evenness Interrupted (Evi) ( Koles et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exosome-dependent release of Wg requires the transmembrane protein Evenness Interrupted (Evi) ( Koles et al, 2012 ). Two further proteins involved in Evi-exosome release, Rab11 and Ykt-6 ( Gross et al, 2012 ; Koles et al, 2012 ), were shown to be direct targets of Dimm ( Hadzic et al, 2015 ). Thus we tested effects of Dimm expression on Evi distribution in the NMJ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general requirement of CPs in neuropeptide and peptide hormone processing and the lack of a CPE gene in the Drosophila genome imply that dCPD is functionally important for the production of bioactive peptides in the fruit fly. This reasoning is supported by a prominent expression of svr in the central nervous system (CNS) and endocrine tissues such as the midgut (Chintapalli, Wang, & Dow, ), as well as by the direct transactivation of svr by the basic helix–loop–helix transcription factor DIMMED which confers a neuroendocrine peptidergic phenotype (Hadžić et al., ). Ectopic expression of svr transgenes in the neurohemal organ of the brain (corpora cardiaca) also affects processing of adipokinetic hormone (AKH; Sidyelyeva et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The general requirement of CPs in neuropeptide and peptide hormone processing and the lack of a CPE gene in the Drosophila genome imply that dCPD is functionally important for the production of bioactive peptides in the fruit fly. This reasoning is supported by a prominent expression of svr in the central nervous system (CNS) and endocrine tissues such as the midgut (Chintapalli, Wang, & Dow, 2007), as well as by the direct transactivation of svr by the basic helix-loophelix transcription factor DIMMED which confers a neuroendocrine peptidergic phenotype (Hadžić et al, 2015). Ectopic expression of svr transgenes in the neurohemal organ of the brain (corpora cardiaca) also affects processing of adipokinetic hormone (AKH; Sidyelyeva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%